Islamic Finance & Securitization Law Would Islamic Finance Have Prevented The Current Global Financial Crisis? - Alhejaili, Mohammad O M (The journal of contemporary issues in business and government, 2021)
The recent financial crisis has encouraged a wide range of individuals to consider whether or not different financing methods could, potentially, have prevented the crisis from taking place, or might have reduced the effects of the crisis, once it had happened. One of the areas of finance that has attracted attention, in recent years, is that of Islamic finance and the equity-based Sharia banking system, which is seen as being an alternative way of running a banking system which may be preferable to the conventional system, when it comes to managing risky situations Before looking in any detail at the various components of the Islamic finance system and the way in which it could, potentially, assist in maintaining economic stability as well as being socially beneficial, a brief background to what is meant by Islamic financing will be undertaken. It is also noted that the recent financial crisis has given the Islamic financial system an opportunity to expand and attract many other individuals who had not previously looked at Islamic finance as a realistic option.